The incidence of injuries across various tennis surfaces: A systematic review - Alexander, S.; Naaz, N.; Fernandes, S. (Coaching and Sport Science Review, 2022)
Tennis players' joints are subjected to enormous loads, with supraphysiological stresses generated at the shoulder and elbow hundreds of times per match. Chronic injuries typically concern the upper extremity while acute injuries typically affect the lower extremities. The type and frequency of injuries have also changed as a result of advancements in equipment and playing surfaces. Top athletes and coaches need some understanding of how the playing surface affects tennis performance. Thus, the purpose of this review is to provide an overview of the most recent research on injuries and playing surface effects in tennis. The main aim of this study was to ascertain whether there is a difference in the incidence of tennis injuries between the four most popular court surfaces, including clay, hard, grass and concrete. Tennis court surfaces have been identified as a factor that influences the occurrence of injuries. The evidence strongly suggests that the surface is a significant component in injury causation and varying surfaces have been found to have considerably different injury rates. A systematic search of published reports was conducted in four electronic databases from 2010 to discover relevant articles relating to tennis injuries and surfaces.